Regulating impact on bystanders in clinical trials: An unsettled frontier. (October 2019) - Eyal, Nir; Kimmelman, Jonathan; Holtzman, Lisa G; Lipsitch, Marc
This article informally reviews key research ethics guidelines and regulations, academic scholarship, and research studies and finds wide variety in how they consider risk to bystanders in medical research (namely, non-participants whom studies nevertheless place at risk). Some of these key sources give no or very little consideration to bystanders, while others offer them the utmost protection (greater than they offer study participants). This unsettled frontier would benefit from a deeper investigation of the ethics of protecting research bystanders.